Laparoscopic vs. open colectomy for T4 colon cancer: A meta-analysis and trial sequential analysis of prospective observational studies - Chen, Peng; Zhou, Hang; Chen, Chuwen; Qian, Xin; Yang, Lie; Zhou, Zongguang (Frontiers in Surgery, 2022)
Abstract Background: To evaluate short- and long-term outcomes of laparoscopic colectomy (LC) versus open colectomy (OC) in patients with T4 colon cancer. Methods: Three authors independently searched PubMed, Embase, Web of Science, Cochrane Library, and Clinicaltrials.gov for articles before June 3, 2022 to compare the clinical outcomes of T4 colon cancer patients undergoing LC or OC. Results: This meta-analysis included 7 articles with 1635 cases. LC could be performed safely and effectively and was associated with lesser blood loss, lesser perioperative transfusion, lesser complications, lesser wound infection, and shorter length of hospital stay. Moreover, there was no significant difference between the two groups in terms of 5-year overall survival (OS), and 5-year disease-free survival (DFS), R0 resection rate, positive resection margin, lymph nodes harvested ≥12, and recurrence. TSA results suggested that the potential advantages of LC on perioperative transfusion and the comparable oncological outcomes in terms of 5-OS, 5-DFS, lymph nodes harvested ≥12, and R0 resection rate is reliable and no need of further study. Conclusions: Laparoscopic surgery is safe and feasible in T4 colon cancer in terms of short- and long-term outcomes. TSA demonstrated that further studies are not needed to evaluate the 5-year OS or DFS, R0 resection rate, positive resection margin status, lymph nodes harvested ≥12 and perioperative transfusion differences between LC and OC.